Aplikasi Android Lukisan Wayang Kamasan Menggunakan Qr Code Sebagai Media Promosi Interaktif ( Studi Kasus: Startup Way’K) - Astawa, Gede Wira; Raditya Putra, I Gusti Lanang Agung; Juliharta, I Gede Putu Krisna (P3M Politeknik Negeri Banjarmasin, 2019)
Kamasan puppet painting is one of the handicrafts that is a Balinese cultural heritage. One of the startups, Way'K, innovates the Kamasan puppet painting into modern products such as wall clock paintings, LED light paintings, and souvenirs in the form of placards. However, this is not enough to increase the selling power of Kamasan puppet painting because based on the results of interviews with startup owners of Way'K tourists are less interested in buying because tourists do not know the meaning and stories contained in the painting, besides promotion and sales are still done conventional considering the development of the era entering the digital era. Therefore, the author makes an Android-based Kamasan puppet painting application that can display painting stories through scanned QR codes on paintings and there are information features and product purchases online through the application. In making the application using the waterfall software approach method and using Use Case modeling and Class Diagram in application design. The application was built using the React Native framework and Laravel framework and tested using the blackbox testing method and the application was successfully designed to wake up and successfully tested with the results as expected. To determine the level of ease of use of the system carried out by the Usability testing method and obtained very good results.